Quality improvement in health care - A fundamental analysis and South African perspective - M. E. Muller (AOSIS, 1996)
This article is based on the opening address that was delivered at a national conference with the launching of the South African Society for Quality in Health Care (SASQuaH). The quality improvement process and principles are analyzed, as well as an exposition of the South African situation. The concepts regarding quality, quality improvement and quality assurance are clarified, the different stakeholders in formalised quality improvement explained, as well as the motives for and principles of quality improvement in health services. The different external and internal mechanisms in quality improvement are analyzed, including the principle of community ownership and international collaboration. Continuous development and capacity building regarding quality improvement is recommended at all levels of health service delivery.